Acceleration Of Financing And Implementation Of Sharia Economy In The Development Of Halal Culinary Area Tourism Solo - Rusli, Moch. (Jurnal Ilmiah Ekonomi Islam, 2024)
Halal industry has become a positive trend in areas of food, fashion, and tourism. In Indonesia, one of the priority areas for halal industry is Halal Culinary Zone in Kauman Solo. Designation this area is aimed at creating a halal value chain ecosystem with Sharia economic principles. This research is descriptive qualitative model, with observations and interviews, data analysis using Creswell's. The results show that several stakeholders play crucial roles in development of Kauman Solo, including Surakarta Government, BI of Surakarta, Sharia Economic Community, BPJPH, UMKM Kauman, BUMN, and private businesses. There are 79 UMKM members, characterized by being home-based and offering their products in front of their homes to tourists visiting the Kauman area. Another distinctive feature is that over 80% of these UMKM businesses have halal certificate. Challenges such as a lack of capital, completeness of administrative documentation and competent human resources are expected to be addressed collectively.